Determining the Heterotic Groups of Selected Grain Maize (Zea mays L.) Inbred Lines using Morphological and Phenological Traits - Mahnaz Oroojloo; Sara Dezhsetan; Behzad Ahmadi; Mohammadreza Shiri; Ali Moghaddam (پژوهشنامه اصلاح گیاهان زراعی)
Extended Abstract Background: The production of new hybrids with high production potential, adaptability to climatic conditions, resistance or tolerance to stresses, and stability in a wide range of environmental conditions have special importance to increase the yield per unit areaTo avoid creating and evaluating a large number of crosses in maize breeding programs based on hybrid production, it is necessary to assign maize lines to heterotic groups. Considering that the heterotic groups have not been determined for the selected maize inbred lines in Iran, this research aims to investigate genetic diversity and determine the heterotic groups in the selected maize lines to make maximum use of heterosis for future breeding programs. Moreover, this research also seeks to classify the selected Iranian maize inbred lines into early, medium, and late ripening groups based on the phenological traits. Methods: Aiming at producing hybrid maize and determining the heterotic groups in this research, 50 selected maize inbred lines produced in Seed and Plant Improvement Institute (SPII) were chosen and evaluated based on their kernel yields, and morphological and phenological traits in a randomized complete block design with three replications in the research field of the Seed and Plant Improvement Institute. Variance analysis and cluster analysis were performed using Ward's method and principal component analysis. Results: In general, significant differences were observed between the traits studied in these selected maize inbred lines. The comparison of the average kernel yield of the inbred lines showed that the inbred line KE77008/1 (from the medium ripening group) produced the highest yield with 4.708 tons per hectare and the inbred line K615/1 (from the early ripening group) produced the lowest yield with 1.016 tons/ha. Moreover, the range of variation was significant for the kernel yield per hectare and other traits among these inbred lines. Therefore, high diversity was observed among the studied lines in terms of kernel yield and the other traits. Selected maize inbred lines based on the phenological traits were classified into three groups, early ripening (105.5-110 days), medium ripening (111-116 days), and late ripening (117.5-122 days). The yield range of the early group differed from 1.01 to 2.74 tons per hectare, the medium group from 1.18 to 3.09 tons per hectare (except for the medium ripening group containing the line KE77008/1 with a performance of 4.70 tons per hectare), and the late group from 1.21 to 3.28 tons per hectare. In genetic analysis, the low difference between the percentage of phenotypic and genotypic coefficients of variation of the traits showed less effects of environmental factors on these traits. The lowest difference was observed between the percentage phenotypic and genotypic coefficients of variation in days to physiological ripening (0.24) and ear height (0.94), which indicates the great effect of genetic factors on the control of these traits. The highest percentage genotypic coefficient of variation was obtained for kernel yield (31.77%), ear height (20.07%), percentage of cob wood (19.96%), the number of kernels per row (17.35%), and 1000-kernel weight (16.8%) traits. In this research, therefore, these traits are valuable in examining the genetic diversity and grouping of maize inbred lines. However, if the percentage of the genetic variation coefficient is higher, more genetic diversity and less environmental influence are observed for that trait. Based on the results of the principal component analysis, the first component explained 25.67% of the total variation. In this component, the highest positive coefficients are attributed to the number of kernels per row (0.518), ear diameter (0.771), leaf number (0.718), plant height (0.668), cob diameter (0.607), ear height (0.50), and kernel moisture at harvest (0.563). The second component explained 19.22% of the total data variance. In this component, the largest positive coefficients belonged to 1000-kernel weight (0.723) and plant height (0.531) traits, and a negative factor coefficient belonged to the number of kernels per row (-0.755). Based on the results of clustering by Ward's method, the selected maize inbred lines were classified into six separate groups. The percentage of deviation from the total average was positive for the yield trait in the first and fourth groups. These two clusters based on the days to physiological ripening trait were medium ripening. The highest days to physiological ripening trait for the lines was recorded in the second cluster) late ripening), it was medium in the first, third, fourth, and sixth clusters (medium ripening), and the lowest value belonged to the fifth cluster (early ripening) compared to the other clusters. Furthermore, the distribution of the lines based on the first and second principle component analysis and cluster analysis were in significant agreement with each other. Conclusion: In general, significant differences in yield and yield components were observed in this set of selected maize inbred lines. Also, a high level of genetic diversity was identified in kernel yield and morphological and phenological traits. Based on the evaluated traits, 50 selected maize inbred lines were generally classified into six groups. Additional investigations based on the produced single cross hybrids (KSC 704, KSC 647, KSC 604, KSC 700, KSC 703, KSC 705, KSC 706, KSC 500, and KSC 260) showed the correct classification of inbred lines and identification of heterotic groups. The heterotic group 5 identified in this study has not played a role in the production of famous single-cross hybrids. Therefore, it is worth paying attention to using the potential of the heterotic group 5 and the other inbred lines attributed to heterotic groups that have not played a role in the production of single-cross hybrids in the production of new hybrids.